Multiple speed assessments: Theory, practice, and research evidence - HERDE, Christoph N. (Institutional Knowledge at Singapore Management University, 2020)
This paper presents Multiple Speed Assessments as an umbrella term to encompass a variety of approaches that include multiple (e.g., 20), short (e.g., 3 min), and often integrated interpersonal simulations to elicit overt behavior in a standardized way across participants. Multiple Speed Assessments can be used to get insight into the behavioral repertoire of a target person in situations sampled from a predefined target domain and their intraindividual variability across these situations. This paper outlines the characteristics and theoretical basis of Multiple Speed Assessments. We also discuss various already existing examples of Multiple Speed Assessments (Objective Structured Clinical Examinations, Multiple Mini-Interviews, and constructed response multimedia tests) and provide an overview of design variations. Finally, we present current research evidence and future research directions related to Multiple Speed Assessments. Although we present Multiple Speed Assessments in the context of personnel selection, it can also be used for assessment in the educational, personality, or clinical psychology field.